Optimization of Machining Parameters and Tool Angle on Surface Quality of Turning Operation Using Taguchi Grey Relational Analysis - Nanang Ali Sutisna; Sapto Agus Nowoasto (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2023)
Turning is an operation using a lathe machine and used to remove metal from the outer diameter of a rotating cylindrical workpiece and reduce the workpiece's diameter while it is rotating. In turning operation, there are various parameters available and there have been several studies and researches that examine the way of optimizing turning parameters to achieve preferable performance. Surface roughness quality is one of the most expected performances. This study aims to optimize the tool angle and machining parameters such as depth of cut, feed, and speed on turning operation to achieve the best surface roughness quality. Turning operations are performed based on the orthogonal array for stainless steel. The optimization of parameters and angle tool in this research used Taguchi Grey relational analysis. This method is expected to minimize the surface roughness of the work piece on turning operation. The Taguchi Grey relational analysis method in this research is meant to calculate and analyze the optimal condition for combined parameters and tool angle to get the optimal surface quality. The result shows that the optimum cutting conditions were cutting speed 70 m/min, depth of cut 0.4 mm, the feed rate 0.2 mm/rev, and cutting-tool angle 91º.